Environmental life cycle assessments of producing maize, grass-clover, ryegrass and winter wheat straw for biorefinery. (20th January 2017) - Parajuli, Ranjan; Kristensen, Ib Sillebak; Knudsen, Marie Trydeman; Mogensen, Lisbeth; Corona, Andrea; Birkved, Morten; Peña, Nancy; Graversgaard, Morten; Dalgaard, Tommy
Abstract: The aim of this study is to assess the potential environmental impacts of producing maize, grass-clover, ryegrass, and straw from winter wheat as biomass feedstocks for biorefinery. The Life Cycle Assessment (LCA) method included the following impact categories: Global Warming Potential (GWP100 ), Eutrophication Potential (EP), Non-Renewable Energy use (NRE), Potential Fresh Water Ecotoxicity (PFWTox) and Potential Biodiversity Damages (PBD). The results showed that GWP100 (in kg CO2 eq, including contribution from soil carbon change) for producing 1 ton of dry matter (t DM) was highest for ryegrass, grass-clover and maize, and lowest for straw. The carbon footprints of ryegrass, grass-clover and maize were affected by including the contribution from soil organic carbon (SOC) changes. Nitrous oxide emissions and emissions related to the production of agro-chemicals (including N-fertilizer) were other hotspots in the carbon footprint. The EP calculated per t DM was highest for grass-clover, ryegrass and maize, and was lowest for straw. NRE use (MJ eq/t DM) was highest for ryegrass, grass-clover and maize and lowest for straw. Major hotspots were diesel use for field operations and agro-chemicals production. The PBD, expressed as Potentially Disappeared Fraction (PDF) showed the highest adverse impact to biodiversity in maize, followed by straw, whereas the results showed relatively lower impact for ryegrass and grass-clover. The PFWTox (CTUe /t DM), at farm level was highest for straw, followed by maize, whereas the values were significantly lower for grass-clover and ryegrass. These variations in ranking of the different biomasses productions using different impact categories for environmental performance showed that it is important to consider a wider range of impact categories for assessing environmental sustainability. Highlights: Environmental impacts of producing biomass at farm gate level are assessed. Soil organic matter turnover and the related changes in soil C sequestration are presented in a temporal perspective. Potential environmental impacts to an agroecosystem including effects of land use change are discussed. Environmental hotspots along the chain of biomass production are discussed.